Study of Challenges, Impact and Solutions in Sustainable Project Management for Green Construction (International Journal of Innovative Research in Computer Science & Technology, 2022)
In recent years, India has seen an explosion  in the environmentally conscious construction industry.  Despite the widespread call for greener buildings to reduce  their environmental impact, studies evaluating their  effectiveness are quite uncommon. Therefore, the purpose of  this research is to examine how well green building  construction projects stick to their timelines, and to make  suggestions that could boost that performance. This study  reports the views of construction experts on the incorporation  of sustainable construction in project administration in  Jammu and Kashmir. In total, data were collected from 122  construction professionals who were randomly selected  through the survey. In different categories, land, water,  waste, energy, human resources and physical resources are  used. The study revealed that the ideas of the success of the  project if it works within the three objectives (time, cost and  quality) influence construction professionals to  underestimate the involvement of sustainability benefits  (environmental, economic and social) in terms of the process  used to measure the project's project. success. However,  most of the buildings in Jammu and Kashmir are very energy  dependent, increasing energy wastage and reducing the  comfort of residents. The result also showed that recycled  construction materials are not fully used in buildings, and  this is due to their unavailability in the industry, the  unsustainable price of the product and the lack of incentives  for the use of such materials. The study concludes that, the  challenge facing the construction industry today is not only  to complete projects on time, cost and quality, but to combine  various constraints such as economic, environmental and  social needs in the construction work. Finally, a set of  proposals was presented with the aim of improving the  effectiveness of the program. The findings of this study will  provide a countermeasure which future green building  construction initiatives may be evaluated.
Keywords: Green Building; Construction; Schedule; Performance; Sustainability